HUBUNGAN TRIASE BERBASIS ANDROID DENGAN TINGKAT KEPUASAN PASIEN DI IGD RSUD TAMAN HUSADA BONTANG - Zainab; Gajali Rahman; Rivan Firdaus (Bajang Institute, 2024)
Introduction: Services in the Emergency Room (IGD) are based on the patient's level of emergency. Patients who arrive early may not necessarily receive medical treatment immediately. Conditions like this cause service to feel slow. Triage is an effort to sort victims before they are treated, based on the emergency level of trauma or disease by considering treatment priorities and existing resources.Objective: Correlation between Android-Based Triage and Patient Satisfaction Levels in the Emergency Room at Taman Husada Bontang Regional Hospital in 2023Method: In this research, the research design used by researchers is analytical research. Correlation analytical design with a cross sectional approach using the bivariate chi square test with a sample size of 86 respondents.Results: Obtained a p value of 0.000 (<α 0.05), meaning that there is a relationship between Android-based triage and emergency room patient satisfaction at Taman Husada Bontang Hospital. Apart from that, an OR (Odd Ratio) of 2.385 was obtained, which means that Android-based triage had an effect 2.385 times on emergency room patient satisfaction at Taman Husada Bontang Hospital.Conclusion: There is a relationship between Android-based triage and emergency room patient satisfaction at Taman Husada Bontang Hospital.Suggestion: It is hoped that it will be able to become a motivator for nurses to improve nursing competence, especially in the use of Android-based triage.